Speaking Anxiety in Oral Presentation-based Assessment: Factors and Strategies - Kustyandari, Febryantika; Sulistyani, Ummi Nur Laila (Universitas Negeri Semarang, 2025)
This study aims to investigates factors contributing to speaking anxiety in oral presentation-based assessments among English Language Teaching (ELT) students and their strategies to overcome it. Speaking is a crucial skill, yet it is often the most challenging for ELT students. While previous research has identified causes of general speaking anxiety, there is a gap in understanding how students specifically manage this anxiety in the context of oral presentation-based assessments, particularly for students learning to be future English teachers. To address this, descriptive qualitative research was conducted with thirty-one fourth-semester ELT undergraduate students at a state university in Indonesia. Data were gathered through a questionnaire adapted from the Public Speaking Class Anxiety Scale (PSCAS) and semi-structured interviews. The findings revealed three main domains of speaking anxiety: discomfort in speaking English, communication anxiety, and test anxiety. Discomfort in speaking English was primarily attributed to the fear of spontaneous speaking and lack of self-confidence due to peer comparison. Communication anxiety was mainly caused by nervousness while waiting to present and the fear of being judged for mistakes. Test anxiety was influenced by the awareness of presentations being graded and the pressure to meet teacher expectations. To manage these anxieties, students employed strategies such as practicing the presentation multiple times, using breathing or relaxation techniques, preparing cue cards, thinking positively, and practicing in front of a mirror or recording themselves. These results provide practical insights for educators to create supportive learning environments and provide students with effective coping mechanisms.